Motivasi Dan Minat Belajar Sains Fisika Siswa Melalui Penerapan Pembelajaran Kooperatif Model Examples Non Examples Di Kelas VIII Smp Negeri 1 Tambang - Muhammad Nasir; Erda Fatriana; Muhammad Sahal (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2010)
This study aimed to determine differences motivation and interest in learning science physics studentsthrough the application of cooperative learning Examples Non Examples model with conventional learningon the subject matter of optical instruments in class VIII SMPN 1 Tambang. The study used a randomizedcontrol-group pretest-posttest. Sampling techniques to test the homogeneity of the population and the sampleis class VIII2 experiment class and control class VIII3. Data collection instrument was a questionnaire ARCSmotivation and interest. Data motivation and interest in learning science physics students were analyzed bydescriptive and inferential. The results obtained by the analysis of motivation and interest in learning sciencephysics students the same for both classes. While the results obtained inferential analysis that the researchhypothesis is rejected, so that there is no significant difference in the motivation and interest of studentsstudying the physics sciences through the application of cooperative learning model Examples Non-Exampleswith conventional learning.